2011
DOI: 10.1002/pbc.23300
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in post‐pubertal adolescent survivors of childhood brain tumors

Abstract: Background Childhood cancer survivors are at high risk for reduced bone mineral density (BMD). Our objective was to determine whether post-pubertal adolescent survivors of brain tumors, whose tumor or treatments placed them at risk for pituitary hormone deficiencies, have low BMD near time of peak bone mass accrual, and to assess risk factors for decreased BMD. Procedure Chart review of 36 post-pubertal adolescents with history of tumor or radiation therapy (RT) of the hypothalamic-pituitary area who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 59 publications
5
30
2
3
Order By: Relevance
“…We also observed increased HR in survivors of CNS tumors, which, as well as the high prevalence of reduced BMD, are common findings in previous studies regarding survivors of CNS tumors . It has been shown that cranial irradiation and growth hormone deficiency are risk factors for osteoporosis in young cancer survivors . Our results also showed survivors of leukemias and CNS tumors to be at high risk for developing osteoporosis although the number was low, and we did not have the information about whether they had irradiation therapy as part of their treatment.…”
Section: Discussionsupporting
confidence: 79%
“…We also observed increased HR in survivors of CNS tumors, which, as well as the high prevalence of reduced BMD, are common findings in previous studies regarding survivors of CNS tumors . It has been shown that cranial irradiation and growth hormone deficiency are risk factors for osteoporosis in young cancer survivors . Our results also showed survivors of leukemias and CNS tumors to be at high risk for developing osteoporosis although the number was low, and we did not have the information about whether they had irradiation therapy as part of their treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Radiation might directly affect BMD by damaging the bone marrow stroma31), but the principal cause is assumed to be deficiencies of hormones such as growth hormone (GH) and sex steroid7,17). Cranial and total body irradiation (TBI) can lead to GHD and central hypogonadism, both of which are associated with BMD deficits32).…”
Section: Pathophysiology Of Bmd Deficits In Ccssmentioning
confidence: 99%
“…Barr et al12) also reported that BMD decreased at the lumbar spine (mean Z-score, -1.05) and femoral neck (mean Z-score, -0.84), with an overall osteopenia prevalence of 47.3%, in brain tumor survivors. Previous reports have showed that survivors of various childhood brain tumors are susceptible to development of fractures and early osteoporosis, especially in association with the risk factor GHD17,45).…”
Section: Prevalence Of Bmd Deficits In Ccssmentioning
confidence: 99%
“…Prolonged treatment with high-dose glucocorticoids in children with ALL may also result in acute complications such as vertebral body compression fractures and avascular necrosis of the bones (165,166). Skeletal recovery was noted to begin shortly after the completion of ALL treatments, but BMD may remain abnormally low for age over several years depending on a variety of factors such as the severity of the deficit at baseline, the presence of other chronic health issues and lifestyle variables (165,166,167 (179,180). Changes in bone remodeling and secondary hyperparathyroidism have been recently described in patients treated with TKI (8).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%